Light-Induced Structural Change in Iridium Complexes Studied by Electron Spin Resonance - Batagin-Neto, A. [UNESP]; Assis, A. P. [UNESP]; Lima, J. F.; Magon, C. J.; Yan, L.; Shao, M.; Hu, B.; Graeff, C. F. O. [UNESP] (Amer Chemical Soc, 2014)
Iridium-based compounds are materials of great interest in the production of highly efficient organic light emitting diodes and several other applications. However, these organometallic compounds present relative low stability due to photodegradation processes still not well understood. In this work we investigated paramagnetic states induced by UV photoexcitation on iridium(III) bis[(4,6-fluorophenyl)-pyridinato-N,C2']picolinate (FIrpic) and iridium(III)-tris(2-phenyl-pyridine) (Ir(ppy)(3)) complexes dispersed in different polymeric matrices by electron spin resonance (ESR). Photogenerated charged states with relatively strong hyperfine interactions were observed and attributed to matrix/complex charge-transfer processes. Measurements of the signal amplitude decay after photoexcitation interruption were performed as a function of temperature. The photoinduced centers are thermally activated with energy barrier between 0.3 and 0.6 eV. Electronic structure calculations suggest that the signals observed by ESR are associated with metastable negatively charged Jr complexes distorted structures.